Penguatan Manajemen Pakan Kambing Peranakan Etawa Untuk Menunjang Produksi Ternak Perah Pada Kelompok Ternak Muda Mandiri - Ica Ayu Wandira; Muhammad Dohi; I Nyoman Sadia; Ryan Aryadin Putra; Ine Karni; Aminurrahman; I Gede Nano Septian; Rezki Amalyadi; Eva Amalia Pratiwi; Luluk Lailatun Nurjanah; Ikhwan Firhamsah (Universitas Mataram, 2026)
This community service activity aims to strengthen the understanding of Peranakan Etawa (PE) goat farmers in the Kelompok Ternak Muda Mandiri of Setanggor Village, Praya Barat District, West Nusa Tenggara, regarding feed management that can support sustainable dairy production. The activity involved 25 farmers. The approach used in this activity is participatory, delivered through materials, in-depth discussions, and question-and-answer sessions, aimed at enhancing farmers' knowledge of feed quantity, quality, and continuity, as well as their connection to livestock production and productivity. The activity results showed an improvement in farmers' understanding of alternative feeds and the importance of efficient feed management. Through communicative, interactive discussions, farmers also discussed the practical problems they face and the solutions that can be applied. Overall, this activity successfully strengthened the farmers' capacity to manage PE goat feed, which is expected to improve productivity and ensure the sustainability of the PE goat farming business in the future.